Hydrothermal carbonization: Temperature influence on hydrochar and aqueous phase composition during process water recirculation. Issue 4 (August 2018) - Köchermann, Jakob; Görsch, Kati; Wirth, Benjamin; Mühlenberg, Jana; Klemm, Marco
Graphical abstract: Highlights: Green waste was hydrothermally treated and process water was reused up to 11 times. Recirculation increased char yield by 4–10 wt% at 180 and 220 °C, respectively. Recirculation increased the energy yield from 70 to 90% at 220 °C. In contrast to 220 °C, accumulated acids reached a maximum concentration at 180 °C. The proportion of detected organic acids on TOC increased by recirculation. Abstract: Hydrothermal carbonization (HTC) is a promising conversion technology for wet biogenic waste material. However, after HTC the process water (PW) is highly enriched with organics. By reutilization of PW, the amount of contaminated waste water can be strongly reduced. However, temperature influence on hydrochar and PW composition during PW recirculation was not examined yet. Therefore, municipal green waste (MGW) was hydrothermally treated at 180 and 220 °C. The PW after HTC was fully reused up to 11 times. Results showed that hydrochar mass yield increases with progressing PW recirculation. Higher temperatures strengthen this effect. However, the higher heating value was not affected by recirculation process. PW analysis showed an accumulation of total organic carbon (TOC), chemical oxygen demand (COD), and organic acids. Most enriched and detected acids are acetic, formic, lactic and propionic acid. Only for formic acid, higher temperatures reduced the accumulation potential. The proportion of detected organic acids on TOC increased and could indicate a degradation of complex organic compounds. Detected phenols accumulated and increased by the factor of 5 at 220 °C. Finally, accumulation kinetics were calculated and showed in good approximation a first order behavior. Over all HTC recirculation steps, no PW had to be disposed.